Attenuation tomography of the upper inner core. Issue 4 (27th April 2017) - Pejić, Tanja; Tkalčić, Hrvoje; Sambridge, Malcolm; Cormier, Vernon F.; Benavente, Roberto
Abstract: The solidification of the Earth's inner core shapes its texture and rheology, affecting the attenuation and scattering of seismic body waves transmitted through it. Applying attenuation tomography in a Bayesian framework to 398 high‐quality PKIKP waveforms, we invert for the apparent Q p for the uppermost 400 km below the inner core boundary at latitudes 45°S to 45°N. We use damping and smoothing for regularization of the inversion, and it seems that the smoothing regularization combined with the discrepancy principle works better for this particular problem of attenuation tomography. The results are consistent with a regional variation in inner core attenuation more complex than hemispherical, suggesting coupling between inner core solidification and the thermal structure of the lowermost mantle. Key Points: Attenuation tomography of the inner core performed from a global data set of waveform correlated measurements Complex regional variations of attenuation The observed pattern of attenuation is not in agreement with commonly accepted spherical degree 1